Identity Conflicts and Complexities in Joyce Carol Oates' Black Girl/White Girl (Raparin Journal of Humanities (RJH), 2025)
Joyce Carol Oates' novel Black Girl/White Girl (2006) entertains a complex relationship of race and contradictions of identities illuminated through the plight of a young black girl and her white college roommate. This research attempts to examine the difficulties and complexities of identity formation for Minette Swift and Genna Hewett-Meade which have been underdeveloped through both individual agency and the sociocultural context. The main instruments dictating their identity construction and contradictions are memory, social expectations, religion, and white guilt. These interconnected factors underscore difficulties in their identity formation and pose challenges to both characters and shape their individual and group experiences. This shared heritage, experienced, accepted, or rejected, gives an illusion of the construction of categories of culture and identity. An illusion irrelevant to the complex interplay among the individual, interpersonal, organizational, and societal contexts and realities. The characters’ Inherited memory serves as a catalyst for resistance and a counter for subjective experiences. Religion becomes central to the internal logic of their identity structure and points to the strengths and weaknesses of their characters. Overemphasis on White guilt results in more defensiveness and negative attitudes. Their immediate context and relationship are influenced by these sources and determinants, resulting in complex and multifaceted levels of discomfort, isolation, ostracization and disengagement.